Ground beam construction process of Complex Islam Pasir Puteh, Kelantan / Siti Nur Atira Mohd Nasir - Mohd Nasir, Siti Nur Atira (Universiti Teknologi MARA, Perak, 2019)
In considering the viability of construction, ground beam that is a significantly challenging engineering endeavour and that if poorly planned executed could cause damage to the existing property. A structural engineer commonly used the ground beam for any part of ground slab for the design in a building construction.